Core turbulent transport in tokamak plasmas: bridging theory and experiment with QuaLiKiz. (26th November 2015) - Bourdelle, C; Citrin, J; Baiocchi, B; Casati, A; Cottier, P; Garbet, X; Imbeaux, F
Abstract: Nonlinear gyrokinetic codes allow for detailed understanding of tokamak core turbulent transport. However, their computational demand precludes their use for predictive profile modeling. An alternative approach is required to bridge the gap between theoretical understanding and prediction of experiments. A quasilinear gyrokinetic model, QuaLiKiz (Bourdelle et al 2007 Phys. Plasmas 14 112501), is demonstrated to be rapid enough to ease systematic interface with experiments. The derivation and approximation of this approach are reviewed. The quasilinear approximation is proven valid over a wide range of core plasma parameters. Examples of profile prediction using QuaLiKiz coupled to the CRONOS integrated modeling code (Artaud et al 2010 Nucl. Fusion 50 043001) are presented. QuaLiKiz is being coupled to other integrated modeling platforms such as ETS and JETTO. QuaLiKiz quasilinear gyrokinetic turbulent heat, particle and angular momentum fluxes are available to all users. It allows for extensive stand-alone interpretative analysis and for first principle based integrated predictive modeling.